THE REALIZATION OF HOTS ON SUMMATIVE TEST ITEMS DESIGNED BY ENGLISH TEACHER GROUP DISCUSSION - Fitriani, Walida Wahid (Jurnal Bahasa Inggris, 2019)
HOTS is becoming trending topic in 21st century. There are three main components of HOTS namely transfer of knowledge, critical thinking and problem solving (Brookhart, 2010: 5-8). Teachers are demanded to stimulate students? critical thinking nowadays. One of the ways is by providing tests based critical thinking. This study was conducted to analyze the realization of HOTS on test items designed by Teachers English Group Discussion (MGMP). The writer employed descriptive qualitative study. The writer took data from summative tests in the first semester which were made by MGMP. The data covered summative tests from the seventh grade, eight grade and the ninth grade. The writer analyzed the data by using Bloom?s Taxonomy as the theoretical framework. There are six levels of cognitive which was revised by Anderson and Karthwoel (2001). Those are remembering, understanding, applying, analyzing, evaluating and creating. The result of the study showed that all of the test items were integrated among LOTS, MOTS and HOTS. Although they had different percentage, it revealed that lower-order thinking skills covered the skill of remembering, understanding, and applying dominates compared to the higher-order thinking skills. Obviously, in the level of higher-order thinking skills, there was only one skill, the skill of analyzing was represented on the test items while the skills of evaluating and creating were not found.